2014
DOI: 10.1007/s00429-013-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrastructural analysis of basket and axo-axonic cell terminals in the mouse hippocampus

Abstract: Three functionally different populations of perisomatic interneurons establish GABAergic synapses on hippocampal pyramidal cells: parvalbumin (PV)-containing basket cells, type 1 cannabinoid receptor (CB 1 )-positive basket cells both of which target somata, and PV-positive axo-axonic cells that innervate axon initial segments. Using electron microscopic reconstructions, we estimated that a pyramidal cell body receives synapses from about 60 and 140 synaptic terminals in the CA1 and CA3 area, respectively. Abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 79 publications
(105 reference statements)
8
63
1
Order By: Relevance
“…The ultrastructure of perisomatic PV + interneurons output synapses formed onto pyramidal cells (identified based on location and ultrastructural characteristics [Takács et al, 2015]) was unaltered in the conditional single and double knock-out mice (Figure 5C–F and Figure 5—figure supplement 1C–F). Moreover, frequency and amplitude of miniature inhibitory postsynaptic currents (mIPSCs) recorded from CA1 neurons in conditional single and double knock-out mice were unchanged (Figure 5G and H and Figure 5—figure supplement 1G and H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrastructure of perisomatic PV + interneurons output synapses formed onto pyramidal cells (identified based on location and ultrastructural characteristics [Takács et al, 2015]) was unaltered in the conditional single and double knock-out mice (Figure 5C–F and Figure 5—figure supplement 1C–F). Moreover, frequency and amplitude of miniature inhibitory postsynaptic currents (mIPSCs) recorded from CA1 neurons in conditional single and double knock-out mice were unchanged (Figure 5G and H and Figure 5—figure supplement 1G and H).…”
Section: Resultsmentioning
confidence: 99%
“…( C ) Ultrastructure of inhibitory synapses in CA1 stratum pyramidale of littermate controls and Nrxn1/3 ex21ΔPV mice. Presumptive PV + cell perisomatic termini were identified by the presence of large mitochondria in the synapses apposed on the membrane of the soma and by their morphology (Takács et al, 2015). ( D ) Average vesicle numbers per active zone and ( E ) average active zone length in nm.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, PV+ interneuron DAI manifested shortly after mTBI and occurred primarily in the perisomatic/AIS domain, prior to the initial branch point of their expansive axonal arbor. Since PV+ interneurons target hundreds of postsynaptic pyramidal neurons (Woodruff et al, 2010; Packer and Yuste, 2011; Taniguchi et al, 2013; Scholl et al, 2015; Takács et al, 2015), disconnection prior to the initial branch point results in widespread, diffuse inhibitory terminal loss. In our recent study, widespread PV+ axonal debris fields within 1 day post-mTBI indicated diffuse terminal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…2,72 Indeed, most basket cells and axo-axonic cells contain considerably higher numbers of mitochondria in dendrites, somata and presynaptic terminals as compared with other interneuron subpopulations and pyramidal cells. 74,[117][118][119][120][121][122][123] This property is highly conserved in various species of mammals. 74,117,124 Moreover, mitochondria of fast-spiking, PV þ interneurons are enriched with proteins such as cytochrome c oxidase (complex IV) and cytochrome c that are crucial for electron transport in the mitochondrial respiratory chain.…”
Section: Mitochondria In Fast-spiking Inhibitory Interneuronsmentioning
confidence: 99%